Operative Management of Cholangiocarcinoma - Lee, Ser Yee; Cherqui, Daniel (Seminars in Liver Disease, 2013)
Cholangiocarcinomas (CCAs) are rare malignancies that originate from the epithelial cells of the bile ducts. It is the second most-common primary liver cancer after hepatocellular carcinoma. Recent epidemiologic studies have shown that the overall incidence and mortality rates of CCAs are increasing. Diagnosis is often challenging due to the difficulty in getting tissue/cytology for confirmation, and it comprises a combination of cross-imaging, tumor markers, histology, and cholangiography. Surgery involving major resections of liver, bile duct, pancreas, and at times adjacent vessels is the only chance for cure. Evaluation should be focused on the assessment of tumor resectability, hepatic reserve, and patient physiological fitness for major surgery. In patients not fit for major surgery, biliary drainage for jaundice is an appropriate intervention and if there is histologic confirmation of a CCA, palliative therapies focused on local and systemic disease control should be considered. The endeavor to expand the indications for liver transplantation reflects the efforts to provide an effective form of therapy for a previously untreatable disease. A multidisciplinary specialized approach should be the platform for providing the best comprehensive care for these patients.
Keywords: cholangiocarcinoma; liver resection; liver transplantation; bile duct cancer